Building Ruddlesden–Popper and Single Perovskite Nanocomposites: A New Strategy to Develop High-Performance Cathode for Protonic Ceramic Fuel Cells - Shi, H.; Su, Chao; Xu, Xiaomin; Pan, Y.; Yang, G.; Ran, R.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2021)
Here a new strategy is unveiled to develop superior cathodes for protonic ceramic fuel cells (PCFCs) by the formation of Ruddlesden–Popper (RP)-single perovskite (SP) nanocomposites. Materials with the nominal compositions of LaSrxCo1.5Fe1.5O10−δ (LSCFx, x = 2.0, 2.5, 2.6, 2.7, 2.8, and 3.0) are designed specifically. RP-SP nanocomposites (x = 2.5, 2.6, 2.7, and 2.8), SP oxide (x = 2.0), and RP oxide (x = 3.0) are obtained through a facile one-pot synthesis. A synergy is created between RP and SP in the nanocomposites, resulting in more favorable oxygen reduction activity compared to pure RP and SP oxides. More importantly, such synergy effectively enhances the proton conductivity of nanocomposites, consequently significantly improving the cathodic performance of PCFCs. Specifically, the area-specific resistance of LSCF2.7 is only 40% of LSCF2.0 on BaZr0.1Ce0.7Y0.2O3−δ (BZCY172) electrolyte at 600 °C. Additionally, such synergy brings about a reduced thermal expansion coefficient of the nanocomposite, making it better compatible with BZCY172 electrolyte. Therefore, an anode-supported PCFC with LSCF2.7 cathode and BZCY172 electrolyte brings an attractive peak power output of 391 mW cm−2 and excellent durability at 600 °C.